2017
DOI: 10.1111/jocn.13756
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence in pregnancy: prevalence and characteristics of the pregnant woman

Abstract: Knowledge of the prevalence and characteristics of pregnant women who experience domestic violence is of paramount importance in planning appropriate strategies for their needs during pregnancy. Results indicate the need for nurses to intervene when warning signs of domestic violence against pregnant women are detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
32
4
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 16 publications
11
32
4
5
Order By: Relevance
“…They believed that as a silent weapon, emotional violence leaves hidden scars that manifest themselves in many ways, such as losing sense of self and integrity, depression, anxiety and suicide attempt. Likewise, previous studies on women who reported experiencing violence for the pregnancy period or postpartum period showed that for these women emotional violence was more disturbing that physical violence (Almedia et al, ; Tho Tran et al, ). Consistent with these findings, in a qualitative study, one of the main emerged themes was that emotional violence hurt more than physical violence (Hatashita, Brykczynski, & Anderson, ).…”
Section: Discussionmentioning
confidence: 86%
“…They believed that as a silent weapon, emotional violence leaves hidden scars that manifest themselves in many ways, such as losing sense of self and integrity, depression, anxiety and suicide attempt. Likewise, previous studies on women who reported experiencing violence for the pregnancy period or postpartum period showed that for these women emotional violence was more disturbing that physical violence (Almedia et al, ; Tho Tran et al, ). Consistent with these findings, in a qualitative study, one of the main emerged themes was that emotional violence hurt more than physical violence (Hatashita, Brykczynski, & Anderson, ).…”
Section: Discussionmentioning
confidence: 86%
“…A violência perpetrada contra as gestantes tem sido fator preocupante em todo o mundo, pois, além de injuriar a mãe, causa sofrimento fetal. Esta pesquisa relevou uma baixa prevalência da violência em gestantes, destoando do que foi encontrado em Almeida 17 , cuja prevalência apresentada no estudo (43,4%) foi considerada alta. Porém, outro estudo também identificou baixa ocorrência do evento nesses públicos 18 .…”
Section: Discussionunclassified
“…Violence was also experienced during pregnancy. According to Almeida et al (2017), violence during pregnancy is associated with greater odds of child physical maltreatment, which underscores the importance of screening pregnant women to prevent violence to young children at an early stage (Chan et al 2012).…”
Section: Discussionmentioning
confidence: 99%